DIVISION OF STAVROPOL PROVINCE INTO DISTRICTS IN 1924: REASONS AND CONSEQUENCES - L. A. Zvereva (Гуманитарные и юридические исследования)
The author made analysis of work of the Soviet authorities in Stavropol Territory before and after division of Stavropol province into districts in 1924.